Black identities inscribed on the streets of Sao Paulo in the 20th century - Silva, Zelia Lopes da [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2018)
This text has as a point of reflection the homages to black people, men and women, inscribed in the streets and squares of Sao Paulo, in different times of the republican period. The chosen ones were projected in the national scene by their accomplishments and by the causes they defended in their contemporaneity. Some tributes express the recognition of black people as protagonist in the defense of the slavery's abolition, such as the bust statue paid by black leaders, which was dedicated to the black poet Luiz Gama, and was affixed in Largo do Arouche square (Nov/1931), and the street names dedicated to the engineers Andre Reboucas (an abolitionist) and Theodoro Sampaio. Symbolically, the Mae Preta sculpture (inaugurated in January 1955 in Largo do Paissandu square) synthesizes the moment of negotiation between white elites and black leaders, in the dispute for the memory and the insertion of the group in the events of the IV Centenary of the City of Sao Paulo in 1954. Therefore, it is intended to argue the meaning and the scope of these honors.
Keywords: Black identities; Black memorials; Street memorials